Twofold - Tan, Raychel Yixin (2014)
This project is to rethink the auspicious motifs lavishly decorated on Chinese ceramic and to redesign the Chinese teacup by extracting essential elements from chosen motifs. In a sense, it can be considered a new branding identity for Chinese tea culture and in hopes to incorporate the drinking and enjoyment of tea into our modern living environment. The wrapping of Japanese aesthetic onto the packaging concept is a fusion between the two countries to bring out the Asian influences with regards to the evolution of tea.